2015
DOI: 10.1016/j.nucmedbio.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of imaging myocardial ischemic/reperfusion injury using 99mTc-labeled duramycin in a porcine model

Abstract: When pathologically externalized, phosphatidylethanolamine (PE) is a potential surrogate marker for detecting tissue injuries. 99mTc-labeled duramycin is a peptide-based imaging agent that binds PE with high affinity and specificity. The goal of the current study was to investigate the clearance kinetics of 99mTc-labeled duramycin in a large animal model (normal pigs) and to assess its uptake in the heart using a pig model of myocardial ischemia-reperfusion injury. Methods The clearance and distribution of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…In addition, 99m Tc-linear-duramycin imaging showed no radioactive uptake in the area of infarction region, confirming 99m Tc-duramycin specific uptake. Although the result of this study was similar to other findings, where the 99m Tc-duramycin is predominantly excreted through the urinary system with relatively low systemic and hepatic background in its mouse model [13,26] . Hence, this study indicated that 99m Tc-duramycin enabled the detection of myocardial cell death effectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, 99m Tc-linear-duramycin imaging showed no radioactive uptake in the area of infarction region, confirming 99m Tc-duramycin specific uptake. Although the result of this study was similar to other findings, where the 99m Tc-duramycin is predominantly excreted through the urinary system with relatively low systemic and hepatic background in its mouse model [13,26] . Hence, this study indicated that 99m Tc-duramycin enabled the detection of myocardial cell death effectively.…”
Section: Discussionsupporting
confidence: 90%
“…It is an ideal target for detecting death including apoptosis and necrosis, which can specifically bind to PE with high affinity and low background [11] . Some studies had shown extensively application of 18 F or 99m Tc labelled duramycin for detecting apoptosis in ischemia reperfusion injury, atherosclerosis, and tumors [12][13][14][15][16] . In this study, we evaluated the feasibility that the 99m Tc-labeled duramycin used to monitor myocardial cell death in a mouse model of acute myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo avidity of 99m Tc-duramycin for cell death has previously been demonstrated in animal models of whole-body irradiation and cerebral and myocardial ischemia and reperfusion (8,10,12). We recently demonstrated the usefulness of 99m Tc-duramycin in an oncology setting showing ability to detect irinotecan-induced tumor apoptosis early (11).…”
Section: Discussionmentioning
confidence: 92%
“…The low molecular weight (MW) of duramycin (∼2 kDa) confers this tracer with favorable pharmacokinetics and biodistribution properties for in vivo imaging of apoptosis [ 16 ]. [ 99m Tc]Duramycin has been successfully used as a probe for the imaging of cell death in animal models of cerebral [ 17 ] and myocardial [ 18 , 19 ] ischemia–reperfusion, accumulating in tissue sites of injury where there is high apoptotic activity. Additionally, this probe was also effectively used to assess tissue damage after whole-body irradiation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%